Wet chemical synthesis of ZnO-CdS composites and their photocatalytic activity. (March 2018) - Zgura, I.; Preda, N.; Socol, G.; Ghica, C.; Ghica, D.; Enculescu, M.; Negut, I.; Nedelcu, L.; Frunza, L.; Ganea, C.P.; Frunza, S.
Graphical abstract: Highlights: ZnO-CdS composites were synthesized by wet chemical method. TEM, correlated SAED pattern, XRD, and SEM confirmed the structure of composites. CdS amount added during composites synthesis influences their morphologies. RhB degradation efficiency is higher for composites than that of pristine ZnO, depending on the catalyst morphology. Abstract: The present study is focused on the wet chemical synthesis and the characterization of ZnO-CdS composites. The X-ray diffraction shows that the composites contain ZnO in hexagonal wurtzite structure and CdS in cubic phase. The scanning/transmission electron microscopy images reveal flower-like structures with different sizes depending on the CdS content. The optical investigations on composites reveal that the reflectance spectra disclose two thresholds of ∼370 nm and ∼460 nm associated with the ZnO and CdS, respectively. The photocatalytic activity measurements evidenced that the degradation efficiency of RhB in the presence of composites is higher comparatively with pristine ZnO, depending on the catalyst morphology, which varies with CdS content and the pH value of RhB solution. The electron paramagnetic resonance revealed the presence of the paramagnetic point defects in the samples. Thus, the wet chemical approaches are suitable for a large scale production of such ZnO-CdS composites having enhanced photocatalytic activity.